Management Strategy for Digital Transformation: A Comprehensive Guidance Approach - Shafirah, Nadya (Journal of Global Economy, Business and Finance, 2025)
In the swiftly changing tapestry of digital transformation, organizations endure innumerable perils and risks that can hinder project success and prevent ongoing business operations. This research paper provides a holistic approach to managing such risks, drawing from established risk management frameworks and real-world examples. First, it underscores how critical it is for organizations to identify risks thoroughly, including how to methodically find potential dangers and weaknesses in their digital transformation programs. The study then dives into risk assessment methodology, arguing that risks should be prioritized based on their potential impact and chance of occurrence using both quantitative and qualitative procedures. The study also examines risk mitigation techniques, emphasizing the need for proactive steps to reduce the probability and impact of hazards that have been recognized. These tactics could be putting in place strong cybersecurity safeguards, putting change management procedures into action, and encouraging an organization-wide risk- awareness culture. The study also emphasizes how crucial it is to continuously evaluate risks over the course of a project. Organizations can promptly identify new risks and modify their mitigation methods by utilizing key performance indicators and risk indicators. All things considered, this document is a useful tool for companies starting their digital transformation journeys because it provides information and tactics for navigating the tricky world of risk management and guaranteeing project success.